Association Between Race/Ethnicity and COVID‐19 Outcomes in Systemic Lupus Erythematosus Patients From the United States: Data From the COVID‐19 Global Rheumatology Alliance. Issue 1 (2nd December 2022) - Ugarte‐Gil, Manuel F.; Alarcón, Graciela S.; Seet, Andrea M.; Izadi, Zara; Montgomery, Anna D.; Duarte‐García, Alí; Gilbert, Emily L.; Valenzuela‐Almada, Maria O.; Wise, Leanna; Sparks, Jeffrey A.; Hsu, Tiffany Y.‐T.; D'Silva, Kristin M.; et al.
Abstract : Objective: To determine the association between race/ethnicity and COVID‐19 outcomes in individuals with systemic lupus erythematosus (SLE). Methods: Individuals with SLE from the US with data entered into the COVID‐19 Global Rheumatology Alliance registry between March 24, 2020 and August 27, 2021 were included. Variables included age, sex, race, and ethnicity (White, Black, Hispanic, other), comorbidities, disease activity, pandemic time period, glucocorticoid dose, antimalarials, and immunosuppressive drug use. The ordinal outcome categories were: not hospitalized, hospitalized with no oxygenation, hospitalized with any ventilation or oxygenation, and death. We constructed ordinal logistic regression models evaluating the relationship between race/ethnicity and COVID‐19 severity, adjusting for possible confounders. Results: We included 523 patients; 473 (90.4%) were female and the mean ± SD age was 46.6 ± 14.0 years. A total of 358 patients (74.6%) were not hospitalized; 40 patients (8.3%) were hospitalized without oxygen, 64 patients (13.3%) were hospitalized with any oxygenation, and 18 (3.8%) died. In a multivariable model, Black (odds ratio [OR] 2.73 [95% confidence interval (95% CI) 1.36–5.53]) and Hispanic (OR 2.76 [95% CI 1.34–5.69]) individuals had higher odds of more severe outcomes than White individuals. Conclusion: Black and Hispanic individuals with SLE experienced more severe COVID‐19 outcomes, which is consistent with findings in the US general population. These results likely reflect socioeconomic and health disparities and suggest that more aggressive efforts are needed to prevent and treat infection in this population.